Licochalcone H Induces Cell Cycle Arrest and Apoptosis in Human Skin Cancer Cells by Modulating JAK2/STAT3 Signaling - Park, Kyung-Ho; Joo, Sang Hoon; Seo, Ji-Hye; Kim, Jumi; Yoon, Goo; Jeon, Young-Joo; Lee, Mee-Hyun; Chae, Jung-Il; Kim, Woo-Keun; Shim, Jung-Hyun (Biomolecules & therapeutics, 2022)
Licochalcone H (LCH) is a phenolic compound synthetically derived from licochalcone C (LCC) that exerts anticancer activity. In this study, we investigated the anticancer activity of LCH in human skin cancer A375 and A431 cells. The 3-(4,5-dimethylthiazol- 2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium (MTS) cell viability assay was used to evaluate the antiproliferative activity of LCH. Cell cycle distribution and the induction of apoptosis were analyzed by flow cytometry. Western blotting assays were performed to detect the levels of proteins involved in cell cycle progression, apoptosis, and the JAK2/STAT3 signaling pathway. LCH inhibited the growth of cells in dose- and time-dependent manners. The annexin V/propidium iodide double staining assay revealed that LCH induced apoptosis, and the LCH-induced apoptosis was accompanied by cell cycle arrest in the G1 phase. Western blot analysis showed that the phosphorylation of JAK2 and STAT3 was decreased by treatment with LCH. The inhibition of the JAK2/STAT3 signaling pathway by pharmacological inhibitors against JAK2/STAT3 (cryptotanshinone (CTS) and S3I-201) simulated the antiproliferative effect of LCH suggesting that LCH induced apoptosis by modulating JAK2/STAT3 signaling.